Recensão: Vincenzo Borghetti and Tim Shephard (eds.), The Museum of Renaissance Music: A History in 100 Exhibits (Turnhout, Belgium, Brepols, 2023), 523 pp., ISBN: 978-2-503-58856-8 - Utidjian, Haig (Revista Portuguesa de Musicologia, 2025)
Vincenzo Borghetti and Tim Shephard (eds.), The Museum of Renaissance Music: A History in 100 Exhibits (Turnhout, Belgium, Brepols, 2023), 523 pp., ISBN: 978-2-503-58856-8